The Effect of Celebrity Endorsement on Purchase Decisions with Brand Awareness and Purchase Intention as Intervening Variables (Survey of “Bestcorn” Consumers, Bulukumba, South Sulawesi) - Rahmat Taufiq; Edy Yulianto; Swasta Priambada (LPPM Universitas PGRI Sumatera Barat, 2024)
This research is motivated by the fluctuation of